DESAIN PENGEMBANGAN GREEN ARCHITECTURE DI KAWASAN DAGO DENGAN PENDEKATAN ARSITEKTUR TRADISIONAL SUNDA - Iswanto, Hadi Yanuar; Priyadi, Adam; Nurtadril, Ikhwan; Pratama, Luthfi (Program Kreativitas Mahasiswa - Penelitian, 2013)
This PKM is come from global warming which to be seriously concern issue around the world. Solution for it has been encourage with carbon emissions reduction program. Another way to support the program is movement of green architecture. This movement emerged as an awareness to create a building with friendly to earth. This movement are to be trending topic around the world. In Indonesia, particularly in Bandung, many developer and owner choose Dago area to build green architecture. Dago is located at North of Bandung and surrounding of hill topography. Dago also has beautiful view which made a reason to place green architecture on there. But, Dago has a special regulation because itâs water conservasion area. So, developed house with green architecture term are interesting to research. Green architecture not only impact to living of humanities but also contribute to preservation of environment. This research are to finding green technology on architecture in Dago. Methods are used in this research is check list system trhrough an interview and observation. Rating did based on GBCI rating tools with appropriate to green building theory and government regulation in North of Bandung, so made the output of research is appropriate with green architecture theory. Minus point on rating component can be complete with Sundanese architecture, because Sundanese architecture has natural characteristics such as water, bamboo, and stone.Â  Â Â Keywords: green architecture, sundanese architecture, bandung